Relative sea-level changes in Crete: reassessment of radiocarbon dates from Sphakia and West Crete - Price, S; Higham, T; Nixon, L; Moody, J (British School at Athens, 2002)
This article is concerned with the recognition and dating of Holocene relative sea-level changes along the coast of west Crete (an island located in the active Hellenic subduction arc of the southern Aegean) and in particular Sphakia. Radiocarbon data for changes in sea levels collected and analysed previously must (a) be recorrected to take into account isotopic fractionation, and (b) recalibrated by using the new marine reservoir value. These new radiocarbon dates are analysed using Bayesian statistics. The resulting calendar dates for changes in sea level are younger than previously assumed. In particular the Great Uplift in western Crete in late antiquity must be dated to the fifth or sixth century AD, not to AD 365. Moreover, recent work on tectonics suggests that the Great Uplift need not have been accompanied by a catastrophic earthquake. Finally, we consider the consequences of the Great Uplift for some coastal sites in Sphakia.